Peculiarities of inflammatory markers in patients with community-acquired pneumonia associated with coronavirus infection - Avgaitis, S.; Sid, E. V.; Сідь, Євген Володимирович (Vancouver : Perfect Publishing, 2024)
The aim of the study was to determine the peculiarities of inflammatory markers in patients with community-acquired pneumonia associated with coronavirus infection.